2015
DOI: 10.1099/mic.0.000044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron on the probiotic properties of the vaginal isolate Lactobacillus jensenii CECT 4306

Abstract: The vaginal microbiota of healthy, fertile women is dominated by lactobacilli. As a defence mechanism, these bacteria produce H 2 O 2 to discourage colonization of the vagina by undesirable micro-organisms. In particular, Lactobacillus jensenii CECT 4306 is a strong producer of H 2 O 2 and has been found to protect itself from the bactericidal effects of this compound through the activity of extracellular peroxidases. However, this peroxidase activity is dependent on the presence of Fe 3+ , which is found in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…All the experiments were performed in triplicate. The adhesion values have been normalized using Lactobacillus rhamnosus GG (LGG) a positive control know by their good adhesion properties to mucin (Martin et al, 2015). Results are presented by the mean and the standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…All the experiments were performed in triplicate. The adhesion values have been normalized using Lactobacillus rhamnosus GG (LGG) a positive control know by their good adhesion properties to mucin (Martin et al, 2015). Results are presented by the mean and the standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the models mentioned above did not mimic the mucus layer, which is the first barrier inoculated strains meet with. Mucin-secreting HT-29-MTX cells might overcome the shortcomings to some extent ( Martín et al, 2015 ). Nevertheless, the composition of mucin produced by HT-29-MTX cells is different from that of mucin derived from the human intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…40 kDa was also detected in MYU 208. This most likely corresponded to GAPDH, as many reports have shown that 40-kDa GAPDH binds to various substances in the intestinal tract, such as mucin, extracellular matrix, and intestinal epithelial cells [25, 28, 50, 51]. However, the protein could not be clearly identified because the band was very weak and showed nonspecific binding.…”
Section: Discussionmentioning
confidence: 89%
“…It is difficult to explain these observations of multibinding by ionic bonds alone. Furthermore, the multiple functionalities of moonlighting proteins, other than their functions as adhesins, are enhanced with tPA- and uPA-mediated plasminogen activation [62], protecting LAB from environmental stress [55, 63,64,65] and stimulating the immune response of the host [48, 51, 66]. We can use these moonlighting proteins as functional markers to select useful probiotic LAB strains in the future.…”
Section: Discussionmentioning
confidence: 99%